Negative electrode sheet, method for manufacturing the same, battery, battery pack, and electric device
Patent Information
- Application Number
- CN202510542815.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-27
AI Technical Summary
然而,由于天然石墨球形化过程中无法避免带来的高内部孔隙率,将造成使用天然石墨的负极片电解液消耗增大、存储衰减劣化等问题;另一方面,由于天然石墨本征的结构特点,例如:层间距小、有序组织尺寸大,将造成使用天然石墨的负极片在嵌锂后有着比其他负极片更大的体积膨胀,这一特征将加速二次电池循环膨胀,降低电芯循环性能
[0027]本发明提供的负极片满足K为0.4~32.4,其中K通过包含天然石墨的负极片的晶体学参数、天然石墨的孔隙密度以及负极片的压实密度关系计算得到。当负极片满足K时,一方面,对负极片的内部孔隙、负极片的综合微晶尺寸以及负极片压实密度的综合调控,可有效降低天然石墨与电解液在循环及存储过程中对活性离子(例如:锂离子)的消耗,提升电池的循环寿命和储存性能;在另一方面,有效提升二次电池负极片的模量和嵌锂量,降低负极片在嵌锂过程中的体积膨胀,进而使电池具高能量密度特性。
Smart Images

Figure CN122991990A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a negative electrode sheet, and more particularly to a negative electrode sheet and its preparation method, a battery, a battery pack, and an electrical device, belonging to the field of secondary battery technology. Background Technology
[0002] With the widespread application of rechargeable batteries in electronic devices, passenger vehicles, and energy storage facilities, consumers are placing higher demands on the energy density and calendar life of these energy storage carriers. From an environmental perspective, with increasing global emphasis on carbon footprint, artificial graphite, which consumes a significant amount of energy during its production, faces increasingly stringent environmental requirements. From a production and cost perspective, reducing process cycles and lowering raw material costs are key to improving production efficiency and reducing the watt-hour cost of battery cells. In summary, using natural graphite as the negative electrode active material for lithium-ion batteries is an effective means to achieve high energy density, reduce raw material carbon emissions, improve production efficiency, and lower raw material processing costs. However, the high internal porosity unavoidable during the spheroidization process of natural graphite will lead to increased electrolyte consumption and deterioration in storage capacity of negative electrode sheets using natural graphite. On the other hand, due to the inherent structural characteristics of natural graphite, such as small interlayer spacing and large ordered structure size, negative electrode sheets using natural graphite will experience greater volume expansion after lithium intercalation than other negative electrode sheets. This characteristic will accelerate the cycle expansion of rechargeable batteries and reduce cell cycle performance.
[0003] Therefore, it is necessary to optimize the negative electrode sheet containing natural graphite to achieve low expansion of the negative electrode sheet using natural graphite and long cycle life, good storage performance and high energy density of the secondary battery. Summary of the Invention
[0004] This invention provides a negative electrode sheet with low expansion characteristics. When this negative electrode sheet is applied to a battery, the battery exhibits long cycle life, good storage performance, and high energy density.
[0005] The present invention also provides a method for preparing a negative electrode sheet, which is simple to operate and can prepare the above-mentioned negative electrode sheet.
[0006] The present invention also provides a battery comprising the above-described negative electrode sheet or a negative electrode sheet prepared by the above-described preparation method, which has long cycle life, good storage performance and high energy density characteristics.
[0007] The present invention also provides a battery pack comprising a plurality of the above-described batteries, the battery pack having long cycle life, good storage performance and high energy density characteristics.
[0008] The present invention also provides an electrical device, which includes the above-described battery or the above-described battery pack.
[0009] The present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a carbon-based material, the carbon-based material comprises natural graphite, and the negative electrode sheet satisfies K, wherein K is 0.4 to 32.4;
[0010] Wherein, K is calculated using Equation 1:
[0011] K = (C 101 +C 002 )×PD×ρ P Formula 1;
[0012] In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PD is the compaction density of the negative electrode sheet, with units of g / cm³. 3 ;ρ P The pore density of the natural graphite in the negative electrode sheet is expressed in mL / g.
[0013] C 101 =1.84×λ / (FWHM) 101 ×cosθ 101 Formula 2;
[0014] C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3;
[0015] In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the half-width at half-maximum (FWHM) of peaks (101) and (002) in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002 λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm.
[0016] The negative electrode as described above, wherein C 101 +C 002 The range is 40nm to 180nm.
[0017] In the negative electrode sheet described above, the D50 particle size of the natural graphite is 12μm to 18μm.
[0018] The negative electrode as described above, wherein ρ P The concentration ranges from 0.005 mL / g to 0.13 mL / g.
[0019] The negative electrode as described above has a PD of 1.4 g / cm³. 3 ~1.85g / cm 3 .
[0020] The negative electrode sheet as described above, wherein the mass content of the natural graphite is 20% to 100% based on the total mass of the negative electrode active material.
[0021] A second aspect of the present invention provides a method for preparing the negative electrode sheet as described above, comprising the following steps:
[0022] 1) A layer of negative electrode active material will be disposed on at least one side surface of the negative electrode current collector;
[0023] 2) The negative electrode active material layer is subjected to roll forming to obtain the negative electrode sheet; the temperature of the roll forming is 120℃~180℃; and / or the roll forming linear pressure is 70MPa~200MPa; and / or the belt speed is 6m / min~10m / min.
[0024] A third aspect of the present invention provides a battery comprising a negative electrode sheet provided in the first aspect of the present invention, or a negative electrode sheet prepared by the preparation method of the second aspect of the present invention.
[0025] A fourth aspect of the present invention provides a battery pack comprising a plurality of batteries connected in series, in parallel or in a mixed manner, wherein the batteries include the batteries provided in the third aspect of the present invention.
[0026] The fifth aspect of the present invention provides an electrical device, including the battery provided in the third aspect of the present invention or the battery pack provided in the fourth aspect of the present invention.
[0027] The negative electrode sheet provided by this invention satisfies K as being between 0.4 and 32.4, where K is calculated based on the relationship between the crystallographic parameters of the negative electrode sheet containing natural graphite, the pore density of natural graphite, and the compaction density of the negative electrode sheet. When the negative electrode sheet satisfies K, on the one hand, the comprehensive control of the internal pores, the overall crystallite size, and the compaction density of the negative electrode sheet can effectively reduce the consumption of active ions (e.g., lithium ions) by natural graphite and electrolyte during cycling and storage, thereby improving the cycle life and storage performance of the battery; on the other hand, it effectively improves the modulus and lithium intercalation capacity of the secondary battery negative electrode sheet, reduces the volume expansion of the negative electrode sheet during lithium intercalation, and thus enables the battery to have high energy density characteristics. Attached Figure Description
[0028] Figure 1 The XRD diffraction pattern of the negative electrode sheet provided in Embodiment 12 of the present invention;
[0029] Figure 2The pore size distribution curve of the negative electrode sheet provided in Embodiment 12 of the present invention. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0031] In existing technological solutions, the following aspects are mainly used to regulate and optimize the negative electrode sheet using natural graphite: ① Reducing the particle size of the active material to reduce the expansion rate of a single active material. However, this solution has certain limitations. Reducing the particle size of the active material cannot directly control the modulus and expansion of the active material. In fact, reducing the particle size of the active material will increase the internal pore density and reduce the storage performance of active ions; ② Reducing the amount of natural graphite used to reduce the impact of natural graphite on the expansion rate of the negative electrode sheet. However, this solution is difficult to meet the design requirements of high energy density, and it cannot solve the impact of the intrinsic properties of natural graphite on battery life performance from the perspective of the negative electrode sheet structure; ③ Reducing the pore density of the active material can reduce the consumption of active ions at the internal pore interface. However, this solution has a large pore density, and its effect on solving the cycle decay problem caused by the expansion of natural graphite is minimal.
[0032] Based on this, the present invention provides a negative electrode sheet, including a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, which includes a carbon-based material, and the carbon-based material includes natural graphite. The negative electrode sheet satisfies K, where K is 0.4 to 32.4.
[0033] Wherein, K is calculated using Equation 1:
[0034] K = (C 101 +C 002 )×PD×ρ P Formula 1;
[0035] In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PD is the compaction density of the negative electrode, with units of g / cm³. 3 ;ρ P The porosity of natural graphite in the negative electrode is expressed in mL / g.
[0036] C 101 =1.84×λ / (FWHM) 101 ×cosθ101 Formula 2;
[0037] C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3;
[0038] In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the full width at half maximum (FWHM) of the (101) and (002) peaks in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002 λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm.
[0039] For example, when FWHM 101 When the value is 0.3°, the value can be converted to radians as follows: 0.3 × π / 180 = 0.005233.
[0040] For example, the value of K includes, but is not limited to, a range of 0.4, 0.5, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 32.4 or any two of these.
[0041] Among them, the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode are derived from the carbon-based materials contained in the negative electrode, especially natural graphite.
[0042] In detail, λ is the wavelength of the cathode ray used in X-ray diffraction, which is determined by the cathode material (i.e., target material) of the X-ray tube and the operating conditions of the X-ray tube. In one specific embodiment, the wavelength of the cathode ray used in X-ray diffraction (copper target Kα) is λ, which is 0.15418 nm.
[0043] The half-peak width (WHM) of the (101) and (002) peaks in the X-ray diffraction pattern of the negative electrode refers to the peak width at half the peak height of the (101) and (002) peaks. It should be noted that the (101) and (002) peaks in the X-ray diffraction pattern of this invention refer to the (101) and (002) peaks of all types of carbon in the negative electrode, including carbon materials existing in the form of negative electrode active materials and carbon materials existing in the form of conductive agents.
[0044] In X-ray diffraction patterns, the full width at half maximum (FWHM) can be used to estimate the average grain size, crystal defects, and phase characteristics of carbon-based materials, especially natural graphite, in negative electrodes.
[0045] The porosity of natural graphite in a negative electrode refers to the volume of pores in the natural graphite within a unit mass of the negative electrode active material layer, which can be tested using mercury intrusion porosimetry. In this invention, the porosity of natural graphite is determined as follows: the negative electrode is tested using a mercury intrusion porosimetry instrument. The test is based on the Washburn equation, r = -2σcosθ / P, where r is the pore diameter of an ideal cylindrical inner hole, σ is the surface tension of mercury, θ is the contact angle of mercury, and P is the mercury intrusion pressure. Under certain test conditions, the surface tension of mercury and its contact angle remain constant. The larger the pore diameter of the sample (negative electrode), the smaller the capillary resistance and the lower the mercury intrusion pressure. Therefore, as the mercury intrusion pressure increases, mercury will gradually intrude from the larger pores into the smaller pores. By testing the negative electrode using the mercury intrusion porosimetry method and converting the results according to the Washburn equation, the relationship curve between pore diameter and mercury intrusion amount, as well as the pore diameter distribution curve, can be obtained. In summary, the porosity of natural graphite in the negative electrode of this invention is obtained by integrating the pore size distribution curve of the negative electrode obtained by mercury intrusion porosimetry and taking pore sizes from 5 nm to 500 nm.
[0046] The compaction density of the negative electrode refers to the bulk density of the negative electrode under a certain pressure. The compaction density of the negative electrode of this invention is determined in the following manner.
[0047] Method for testing the compaction density of the negative electrode sheet: 1) Disassemble the secondary battery after complete discharge to obtain the negative electrode sheet; immerse the negative electrode sheet in dimethyl carbonate (DMC) solvent for 10-20 minutes to clean the residual electrolyte, and then dry the negative electrode sheet; 2) Take the above negative electrode sheet and cut out small circular pieces of a certain diameter. Scrape off the coating layer on one side of the small circular piece with a ceramic scraper (or polish it off with sandpaper), and obtain the total weight of the coating on one side of the small circular piece. Calculate the weight of the coating on one side of the small circular piece per unit area, which is the single-sided areal density of the negative electrode active material layer. Calculate the compaction density of the negative electrode sheet by dividing the single-sided areal density of the negative electrode sheet by the thickness of the single-sided negative electrode active material layer.
[0048] The negative electrode sheet requires a certain rolling and shaping process during its preparation. However, the existing rolling and shaping process makes it difficult to optimize the crystal structure and internal pores of natural graphite, resulting in a high expansion rate of the negative electrode sheet and consumption of electrolyte and active ions. Consequently, the cycle performance, storage performance and energy density of the secondary battery are poor.
[0049] When the negative electrode sheet provided by this invention has a K value of 0.4 to 32.4, the battery exhibits long cycle life, good storage performance, and high energy density characteristics when used in a battery.
[0050] After extensive experimentation and analysis of the results, the inventors preliminarily concluded that the reasons for the poor performance are as follows: the energy density and lifespan characteristics of the negative electrode are mainly affected by the crystallographic parameters of the negative electrode containing natural graphite, the internal porosity of the natural graphite, and the compaction density of the negative electrode. Regarding crystallographic parameters, on the one hand, the ordered structural size (i.e., crystallographic parameters) of the carbon-based material including natural graphite determines the specific capacity of the negative electrode active material. A higher ordered lattice size means a higher proportion of natural graphite in the carbon-based material can form LiC6 layered compounds. Furthermore, the larger the ordered lattice size, the lower the modulus of the carbon-based material including natural graphite, the stronger its compaction ability, and the higher the energy density of the resulting battery. On the other hand, as the size of the crystallographic parameters increases, the expandable unit size of the carbon-based material including natural graphite increases, leading to greater volume expansion during charge and discharge, and a decrease in cycle stability. Due to its processing technology, natural graphite contains a large number of pores, which consume active lithium ions upon contact with the electrolyte, affecting battery storage and cycle stability. Increasing the compaction density of the negative electrode will improve the volumetric energy density of the battery, but excessively high compaction density will cause volume expansion and particle rearrangement of the negative electrode during cycling, which is detrimental to the battery's lifespan performance.
[0051] Based on the above reasons, this invention comprehensively analyzes the main parameters of the negative electrode that affect the battery's energy density and lifespan performance, and obtains the following relationship: K = (C 101 +C 002 )×PD×ρ P Furthermore, by setting the K value to 0.4–32.4, the battery can achieve long cycle life, good storage performance, and high energy density.
[0052] Furthermore, in one specific embodiment of the present invention, C 101 +C 002 The range is 40nm to 180nm.
[0053] In detail, C 101 +C 002 Including but not limited to 40nm, 50nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, or any combination thereof.
[0054] Crystallographic parameters determine the size of the expandable crystal units after active ions intercalate into carbon-based materials, including natural graphite, to form layered compounds, further affecting the expansion ratio of the negative electrode. As crystallographic parameters increase, the true density increases, and the size and proportion of the ordered structure in carbon-based materials, including natural graphite, increase. This leads to a higher volume expansion ratio during lithium intercalation, resulting in faster SEI film rupture and repair during reciprocating charge and discharge cycles, thus accelerating the cycle consumption rate. On the other hand, the size of the ordered structure determines the reversible capacity of carbon-based materials, including natural graphite, through the formation of layered compounds, thus affecting the material's energy density. Experimental verification shows that crystallographic parameters in the range of 40nm to 180nm can not only reduce the reversible expansion ratio of the negative electrode but also ensure the energy density of the secondary battery.
[0055] Furthermore, in one specific embodiment of the present invention, the porosity ρ of the natural graphite in the negative electrode sheet is... P The concentration ranges from 0.005 mL / g to 0.13 mL / g.
[0056] In detail, ρ P This includes, but is not limited to, ranges of 0.005 mL / g, 0.01 mL / g, 0.02 mL / g, 0.03 mL / g, 0.04 mL / g, 0.05 mL / g, 0.06 mL / g, 0.07 mL / g, 0.08 mL / g, 0.09 mL / g, 0.10 mL / g, 0.11 mL / g, 0.12 mL / g, 0.13 mL / g, or any combination thereof.
[0057] When the porosity of natural graphite in the negative electrode is within the above range, it can further increase the lithium-ion storage capacity, provide a richer charge transport path, promote lithium-ion diffusion, and alleviate the side reactions between the negative electrode and the electrolyte, thereby enabling the secondary battery to have high energy density and long cycle life.
[0058] In one specific embodiment of the present invention, PD is 1.4 g / cm³. 3 ~1.85g / cm 3 .
[0059] Specifically, the compaction density (PD) of the negative electrode sheet includes, but is not limited to, 1.4 g / cm³. 3 1.45g / cm 3 1.5g / cm 3 1.55g / cm 3 1.6g / cm 3 1.65g / cm 3 1.7g / cm 3 1.75g / cm 3 1.8g / cm 31.85g / cm 3 Or the range formed by any two of them.
[0060] When the compaction density of the negative electrode is within the above range, it helps to further balance the energy density of the battery, especially the volumetric energy density.
[0061] In one specific embodiment of the present invention, the mass content of natural graphite is 20% to 100% based on the total mass of the negative electrode active material.
[0062] In detail, based on the total mass of the negative electrode active material, the mass content of natural graphite includes, but is not limited to, a range of 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any combination thereof. By controlling the content of natural graphite within the above range, the performance of the negative electrode sheet can be better regulated based on the relationship defined in this invention, and the higher the content of natural graphite, the more precise the regulation.
[0063] Wherein, based on the total mass of the negative electrode active material, when the mass content of natural graphite is less than 100%, the negative electrode sheet also includes other types of negative electrode active materials. This invention does not limit the specific type of other types of negative electrode active materials, and can select at least one of the negative electrode active materials commonly used in the field, such as artificial graphite (including graphite materials processed from raw materials such as petroleum coke, needle coke, and isotropic coke), hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), and tin-based negative electrode materials (mainly including tin and tin alloys).
[0064] Furthermore, in one specific embodiment of the present invention, the D50 particle size of the natural graphite is 12μm to 18μm. A D50 particle size within this range is beneficial for compacting the internal voids of the natural graphite during the rolling process of the negative electrode sheet, thereby increasing the cycle performance of the battery.
[0065] In this invention, "particle size D50" refers to the particle size corresponding to a cumulative volume percentage of 50%.
[0066] The method for testing the particle size D50 of natural graphite is as follows: using SEM images at 5000x magnification, the longest diameter of approximately 300 individual graphite particles is statistically analyzed, and the data distribution is calculated to determine the particle size D50 of natural graphite. The SEM images can be obtained by scanning the surface of the negative electrode or by scanning the cross-section of the negative electrode; this invention application does not impose any limitation on the method.
[0067] A second aspect of the present invention provides a method for preparing a negative electrode sheet according to the first aspect, comprising the following steps:
[0068] 1) A layer of negative electrode active material is disposed on at least one side surface of the negative electrode current collector;
[0069] 2) Roll pressing is performed on the negative electrode active material layer to obtain a negative electrode sheet; the rolling temperature is 120℃~180℃; and / or the rolling linear pressure is 70MPa~200MPa; and / or the belt speed is 6m / min~10m / min.
[0070] The preparation method provided by this invention adopts a hot rolling process. By controlling the temperature, pressure and rolling speed of the hot rolling process, the internal pores of the natural graphite material in the negative electrode and the lattice parameters of the carbon-based material in the negative electrode are optimized to obtain a negative electrode that meets the requirements of this solution, thereby enabling the battery to have long cycle life, good storage performance and high energy density characteristics.
[0071] For example, the temperature of the roll forming process can be any two of the following values: 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃. The roll forming linear pressure can be any two of the following values: 70MPa, 80MPa, 90MPa, 100MPa, 110MPa, 120MPa, 130MPa, 140MPa, 150MPa, 160MPa, 170MPa, 180MPa, 190MPa, 200MPa. The belt conveyor speed can be any two of the following values: 6m / min, 7m / min, 8m / min, 9m / min, 10m / min.
[0072] The thickness of the negative electrode sheet after roll forming is 150μm to 200μm. Negative electrode sheets with a thickness range of 150μm or 200μm can better meet the requirements of the roll forming process, balance the requirements of heat conduction, stress dispersion and negative electrode sheet forming, and obtain a negative electrode sheet with better performance.
[0073] For example, the thickness of the negative electrode sheet after roll forming includes, but is not limited to, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, or any combination thereof.
[0074] A third aspect of the present invention provides a battery comprising a negative electrode sheet according to the first aspect or a negative electrode sheet prepared by the preparation method of the second aspect.
[0075] It is conceivable that, in addition to the aforementioned negative electrode, the battery of the present invention also includes a positive electrode, an electrolyte, and a separator.
[0076] Furthermore, in a specific embodiment of the present invention, the positive electrode active material in the positive electrode sheet includes one or more combinations of polyanionic materials such as lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, and lithium manganese iron phosphate, as well as layered positive electrode active materials such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.
[0077] Furthermore, in one specific embodiment of the present invention, the D50 particle size of the positive electrode active material is 0.5 μm to 10 μm. A D50 particle size within this range is advantageous for compatibility with the negative electrode sheet.
[0078] For example, the D50 particle size of the positive electrode active material includes, but is not limited to, a range of 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any combination thereof.
[0079] The method for testing the particle size D50 of the positive electrode active material is as follows: using SEM images at 5000x magnification, the maximum diameter of approximately 300 positive electrode active materials is statistically analyzed, and the data distribution is calculated to determine the particle size D50 of the positive electrode active material. The SEM images can be obtained by scanning the surface of the positive electrode sheet or by scanning the cross-section of the positive electrode sheet; this invention application does not impose any limitation on this method.
[0080] Furthermore, in a specific embodiment of the present invention, the thickness of the positive electrode sheet is 160μm to 240μm. When the positive electrode sheet with the above thickness range is assembled into a battery with the negative electrode sheet of the present application, the electrode thickness is highly compatible, which is beneficial to balancing the diffusion resistance of lithium ions in the positive and negative electrodes and increasing the overall performance of the battery.
[0081] For example, the thickness of the positive electrode sheet includes, but is not limited to, any two of the following: 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, and 240 μm.
[0082] In this invention, the thickness of the positive electrode or negative electrode refers to the total thickness of the active material layer (positive electrode corresponds to the positive active material layer, negative electrode corresponds to the negative active material layer) and the current collector (positive electrode corresponds to the positive current collector, negative electrode corresponds to the negative current collector).
[0083] This invention does not strictly limit the choice of electrolyte, and may include one or more solvents commonly used in current battery electrolytes, as well as lithium salts commonly used in current electrolytes. For example, the solvent may include at least one of ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone; the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0084] This invention does not strictly limit the choice of separator material. It can be one of the separator materials commonly used in batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.
[0085] In the preparation of lithium-ion batteries, the positive electrode, separator, and negative electrode are wound or stacked to obtain bare cells, which are then packaged into pre-stamped aluminum-plastic film bags or battery casings. After the packaged batteries are dried at 85°C, electrolyte is injected into the dried batteries. After the batteries are left to stand, formed, and sealed, the preparation of the lithium-ion battery is completed.
[0086] A fourth aspect of the present invention provides a battery pack comprising a plurality of batteries connected in series, in parallel or in a mixed manner, the batteries including the batteries of the third aspect.
[0087] The battery pack of the present invention can be composed of two or more batteries from the third aspect connected in series, parallel or mixed, wherein the connection method can be one or more of ultrasonic welding, resistance welding and laser welding.
[0088] Because the battery pack of the present invention includes the above-mentioned battery, it also has advantages such as long cycle life, good storage performance and high energy density.
[0089] The fifth aspect of the present invention provides an electrical device, including a battery as described in the third aspect or a battery pack as described in the fourth aspect.
[0090] This invention does not limit the specific types of electrical equipment, and may include any equipment that requires batteries to power it, such as electric vehicles, mobile phones, smart home devices, robots, drones, e-cigarettes, and speakers.
[0091] The electrical equipment provided by the present invention includes the above-mentioned battery or battery pack, and therefore has good electrochemical performance and stability.
[0092] The negative electrode sheet provided by the present invention will be described in detail below through specific embodiments.
[0093] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0094] Example 1
[0095] The method for preparing the negative electrode sheet provided in this embodiment includes the following steps:
[0096] 1. Preparation of negative electrode sheet: Mix negative electrode active material (100wt% natural graphite), conductive agent carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) in a mass ratio of 95.4:0.9:1.5:2.2, add deionized water, and stir in a vacuum mixer until a uniform slurry is formed; coat the negative electrode slurry onto the negative electrode current collector copper foil, and bake in an oven at 100℃ until dry.
[0097] 2. Negative electrode rolling: The dried negative electrode sheet is hot rolled at a rolling temperature of 130℃, a rolling linear pressure of 170MPa, and a belt speed of 8m / min. After slitting, the negative electrode sheet is obtained. The D50 of natural graphite is approximately 15μm, and the thickness of the prepared negative electrode sheet is 190μm.
[0098] Example 2
[0099] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 140℃ and the rolling pressure is 100MPa.
[0100] Example 3
[0101] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that the negative electrode active material is composed of 10 wt% natural graphite and 90 wt% artificial graphite.
[0102] Example 4
[0103] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 20wt% natural graphite and 80wt% artificial graphite; the rolling pressure during the negative electrode rolling process is 120MPa.
[0104] Example 5
[0105] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 30wt% natural graphite and 70wt% artificial graphite; the rolling pressure during the negative electrode rolling process is 120MPa and the belt speed is 7m / min.
[0106] Example 6
[0107] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 20wt% natural graphite and 80wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 150℃, the rolling pressure is 130MPa, and the belt speed is 7m / min.
[0108] Example 7
[0109] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that the rolling temperature during the negative electrode rolling process is 150℃, the rolling pressure is 150MPa, and the belt speed is 8m / min.
[0110] Example 8
[0111] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that the rolling temperature during the negative electrode rolling process is 150℃, the rolling pressure is 150MPa, and the belt speed is 6m / min.
[0112] Example 9
[0113] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that the rolling temperature during the negative electrode rolling process is 160℃, the rolling pressure is 160MPa, and the belt speed is 8m / min.
[0114] Example 10
[0115] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 40wt% natural graphite and 60wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 130℃, the rolling pressure is 110MPa, and the belt speed is 6m / min.
[0116] Example 11
[0117] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the negative electrode active material is composed of 25wt% natural graphite and 75wt% artificial graphite; the rolling temperature during the negative electrode rolling process is 170℃, the rolling pressure is 170MPa, and the belt speed is 10m / min.
[0118] Example 12
[0119] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the rolling temperature is 120℃, the rolling linear pressure is 150MPa, the belt speed is 9m / min, and the negative electrode sheet is obtained after slitting. The D50 of natural graphite is approximately 12μm.
[0120] Example 13
[0121] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the rolling temperature is 130℃, the rolling linear pressure is 190MPa, the belt speed is 9m / min, and the negative electrode sheet is obtained after slitting. The D50 of natural graphite is approximately 18μm.
[0122] Example 14
[0123] The preparation method of the negative electrode sheet in this embodiment is basically the same as that in Example 2, except that: the rolling temperature is 150℃, the rolling linear pressure is 160MPa, the belt speed is 8m / min, and the negative electrode sheet is obtained after slitting. The D50 of natural graphite is approximately 18μm.
[0124] Comparative Example 1
[0125] The preparation method of the negative electrode sheet in this comparative example is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 25℃, the rolling pressure is 200MPa, and the belt speed is 4m / min.
[0126] Comparative Example 2
[0127] The preparation method of the negative electrode sheet in this comparative example is basically the same as that in Example 1, except that: the negative electrode active material is composed of artificial graphite and does not contain natural graphite; the rolling temperature during the negative electrode rolling process is 100℃, the rolling line pressure is 60MPa, and the belt speed is 11m / min.
[0128] Comparative Example 3
[0129] The preparation method of the negative electrode sheet in this comparative example is basically the same as that in Example 1, except that the rolling temperature during the negative electrode rolling process is 100℃, the rolling pressure is 210MPa, and the belt speed is 5m / min.
[0130] Test case
[0131] 1. XRD (C 101 +C 002 )test
[0132] All negative electrode sheets provided in the embodiments and comparative examples were used as samples, and the samples were tested respectively, including the following steps:
[0133] 1) Lay the negative electrode flat on the sample plate and perform XRD tests in an X-ray diffractometer to obtain the XRD spectrum. Record the wavelength λ (in nm) of the cathode rays used in the XRD test. The XRD test conditions are as follows: use copper Kα rays as the cathode rays, use 40kV and 20mA to excite the cathode ray source to generate X-rays, the test scan speed is 5° / min, and use a Kβ filter to remove the influence of Kβ rays on the peak shape and position of the spectrum.
[0134] 2) From the obtained XRD pattern of the negative electrode, obtain the diffraction angle 2θ (in °) of the diffraction peaks corresponding to the (101) and (002) crystal planes, and the half-width at half-peak (i.e., the diffraction angle corresponding to 1 / 2 peak height, in radians) of these two diffraction peaks. Then, calculate C according to Equations 2 and 3. 101 With C 002 Value, and calculate C 101 +C 002 It should be noted that the full width at half maximum (FWHM) of a diffraction peak on a specific crystal plane directly read from an XRD pattern is measured in degrees (°). When calculating the value of parameter K, the FWHM value in degrees needs to be converted to a value in radians.
[0135] Figure 1 The XRD diffraction pattern of the negative electrode provided in Example 12 is shown below. For easier observation and analysis, the diffraction peaks appearing in the angle range of 43.0° to 47.0° were magnified. Figure 1 It can be seen that θ 101 = 22.2605°, θ 002 =13.2641°, FWHM 101 (°) = 0.214, FWHM 002 (°) = 0.134, and C can be calculated using the formula. 101 =82.11, C 002 =60.55, C 101 +C 002 =142.66.
[0136] 2. Pore density test
[0137] The pore size distribution of the negative electrode sheets provided in all embodiments and comparative examples was determined by mercury intrusion porosimetry in GB / T 21650.1-2008 / ISO 15901-1. The pore size distribution curves of the negative electrode sheets tested by mercury intrusion porosimetry were extracted, and the pore density of natural graphite was obtained by integrating the pore size distribution curves in the pore size range of 5 nm to 500 nm.
[0138] in, Figure 2 The pore size distribution curve of the negative electrode sheet provided in Example 12 is obtained by... Figure 2It is known that the porosity of the natural graphite in Example 12 is 0.115 mL / g.
[0139] 3. Negative electrode compaction density test
[0140] The compaction density test method for the negative electrode sheet can be as follows: cut the negative electrode sheet into small circular pieces of a certain size, measure the weight of the negative electrode dressing in the small circular piece per unit area, calculate the areal density, and measure the thickness of the negative electrode dressing. The compaction density is then calculated by the negative electrode sheet areal density / (electrode sheet thickness - current collector thickness).
[0141] The test results for the above parameters are shown in Tables 1A and 1B, and C is calculated for all embodiments and comparative examples. 101 C 002 C 101 +C 002 ρ p Substituting PD into Equation 1, the K values of the negative electrode sheets provided in all embodiments and comparative examples were calculated. Specific results are shown in Tables 1A and 1B.
[0142] Table 1A
[0143]
[0144] Table 1B
[0145]
[0146] 4. Lithium-ion battery preparation and testing
[0147] Positive electrode preparation:
[0148] Lithium iron phosphate with a D50 particle size of 1 μm was used as the positive electrode active material. This positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 96:2:2. N-methylpyrrolidone (NMP) solvent was added, and the mixture was stirred into a homogeneous slurry under vacuum. The positive electrode slurry was sieved (through a 200-mesh sieve) and uniformly coated onto aluminum foil as the positive electrode current collector. After drying in an oven at 120°C, it was rolled and slit to obtain a compacted density of 2.7 g / cm³. 3 The positive electrode plate.
[0149] Electrolyte preparation: Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then dry lithium salt LiPF6 is added to dissolve in the mixed solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0150] Diaphragm preparation: Polyethylene film is selected as the diaphragm and cut into diaphragm sheets.
[0151] Preparation of lithium-ion batteries: The positive electrode sheet, separator sheet and negative electrode sheet provided in all embodiments and comparative examples are stacked in sequence. The separator sheet must completely isolate the positive electrode sheet and the negative electrode sheet. Then, the stacked positive electrode sheet, separator sheet and negative electrode sheet are put into an aluminum-plastic film soft package, electrolyte is injected, and after vacuum sealing, standing, formation, cutting and sealing and other processes, a lithium-ion battery is obtained.
[0152] The prepared lithium-ion batteries were tested for the following performance characteristics:
[0153] (1) Energy density test:
[0154] Weigh the battery at 25℃; under the same conditions, charge and discharge the prepared lithium-ion battery at a 1C rate, with a charging and discharging voltage range of 2.0V to 3.8V; record the actual discharge amount. The ratio of the battery's actual 1C discharge energy to the volume of the negative electrode is the battery's volumetric energy density, and the specific results are shown in Table 2.
[0155] (2) Storage performance test:
[0156] The prepared lithium-ion battery was charged and discharged at a rate of 0.5C at 25℃, with a charge / discharge voltage range of 2.0V to 3.8V. The actual discharge amount recorded at this time is the nominal capacity. The lithium-ion battery was then charged to the cutoff voltage at a rate of 1C, with a charge / discharge voltage range of 2.0V to 3.8V. The lithium-ion battery was stored in a 25℃ constant temperature chamber for 28 days. At 25℃, the lithium-ion battery was discharged at a rate of 1C, and the actual discharge amount recorded at this time is the capacity after storage. The 28-day cycle retention rate is calculated as the capacity after storage divided by the nominal capacity, expressed as a percentage (%). Specific results are shown in Table 2.
[0157] (3) Cyclic performance test:
[0158] The prepared lithium-ion battery was charged and discharged at a rate of 0.5C at 25℃, with a charge-discharge voltage range of 2.0V to 3.8V. Full charge-discharge cycle tests were conducted until the capacity of the lithium-ion battery decayed to 80% of its initial capacity. The number of cycles was recorded. The specific results are shown in Table 2.
[0159] (4) Negative electrode expansion rate test:
[0160] The battery, after undergoing 10 cycles of room temperature cycling performance testing, was discharged to 0% SOC and disassembled in a glove box. The negative electrode was removed, and its thickness was measured using a micrometer. The change in thickness compared to the electrode thickness after capacity testing was recorded as the electrode expansion rate after 10 cycles. The specific results are shown in Table 2.
[0161] Table 2
[0162]
[0163]
[0164] By combining Tables 1A, 1B, and 2, the following conclusions can be drawn:
[0165] 1) By comparing the preparation process and parameters of the negative electrode sheet of Example 1 and Comparative Example 1, as well as the data of Experimental Battery 1 and Comparative Battery 1, it can be seen that at room temperature, the K value of the negative electrode sheet obtained at a lower belt speed is relatively large, which leads to a relatively poor storage capacity retention rate and cycle performance of the battery, and a higher electrode sheet expansion rate.
[0166] 2) By comparing the negative electrode preparation process and parameters of Example 1 and Comparative Example 2, as well as the data of Experimental Battery 1 and Comparative Battery 2, it can be seen that when there is no natural graphite in the negative electrode active material, the K value of the negative electrode is <0.4. Therefore, the energy density, 28-day storage capacity retention rate and cycle capacity retention rate of the battery are relatively poor, especially the energy density of the battery is significantly lower.
[0167] 3) By comparing the negative electrode preparation processes and parameters of Examples 1 and 2 with those of Comparative Example 3, and the corresponding battery data, it can be seen that changing the electrode rolling conditions significantly affects the crystallographic parameter C of the electrode. 101 +C 002 The compressive density and pore density are important factors. When these three factors allow the K value to be in the range of 0.4 to 32.4, the battery has a high energy density, storage capacity retention rate, cycle capacity retention rate, and low electrode expansion. However, the K value of Comparative Example 3 is >32.4, and its energy density, storage capacity retention rate, cycle capacity retention rate, and electrode expansion rate are relatively low.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The device includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, which includes a carbon-based material, which includes natural graphite. The negative electrode sheet satisfies K, where K is 0.4 to 32.
4. Wherein, K is calculated using Equation 1: K = (C 101 +C 002 )×PD×ρ P Formula 1; In Equation 1, C 101 and C 002 The crystallographic parameters of the carbon-based material are calculated using Equations 2 and 3, respectively, with units of nm; PD is the compaction density of the negative electrode sheet, with units of g / cm³. 3 ;ρ P The pore density of the natural graphite in the negative electrode sheet is expressed in mL / g. C 101 =1.84×λ / (FWHM) 101 ×cosθ 101 Formula 2; C 002 =0.89×λ / (FWHM) 002 ×cosθ 002 Formula 3; In Equations 2 and 3, FWHM 101 and FWHM 002 θ represents the half-width at half-maximum (FWHM) of peaks (101) and (002) in the X-ray diffraction pattern of the negative electrode, respectively, in radians; 101 and θ 002 λ represents half the 2θ values of the (101) peak and (002) peak in the X-ray diffraction pattern of the negative electrode, respectively, both in °; λ is the wavelength of the cathode ray used in X-ray diffraction, in nm.
2. The negative electrode sheet according to claim 1, characterized in that, C 101 +C 002 The range is 40nm to 180nm.
3. The negative electrode sheet according to claim 1 or 2, characterized in that, The D50 particle size of the natural graphite is 12μm to 18μm.
4. The negative electrode sheet according to any one of claims 1-3, characterized in that, ρ P The concentration ranges from 0.005 mL / g to 0.13 mL / g.
5. The negative electrode sheet according to any one of claims 1-4, characterized in that, PD is 1.4 g / cm³ 3 ~1.85g / cm 3 .
6. The negative electrode sheet according to any one of claims 1-5, characterized in that, Based on the total mass of the negative electrode active material, the mass content of the natural graphite is 20% to 100%.
7. A method for preparing a negative electrode sheet according to any one of claims 1-6, characterized in that, Includes the following steps: 1) A layer of negative electrode active material is disposed on at least one side surface of the negative electrode current collector; 2) The negative electrode active material layer is subjected to roll forming to obtain the negative electrode sheet; the temperature of the roll forming is 120℃~180℃; and / or the roll forming linear pressure is 70MPa~200MPa; and / or the belt speed is 6m / min~10m / min.
8. A battery, characterized in that, This includes the negative electrode sheet as described in any one of claims 1-6, or the negative electrode sheet prepared by the preparation method described in claim 7.
9. A battery pack comprising a plurality of batteries connected in series, parallel, or mixed connections, characterized in that, The battery includes the battery of claim 8.
10. An electrical appliance, characterized in that, Includes the battery as described in claim 8, or the battery pack as described in claim 9.